2014
DOI: 10.1159/000357154
|View full text |Cite
|
Sign up to set email alerts
|

Association of Low Serum Complement C3 with Reduced Patient and Renal Survival in Antimyeloperoxidase-Associated Small-Vessel Vasculitis

Abstract: Objective: This study aimed to determine the value of hypocomplementemia in predicting the renal and patient survival of patients with antineutrophil cytoplasmatic antibody-associated vasculitis (AAV). Methods: A retrospective analysis of 30 consecutive patients who were diagnosed with AAV and followed at our hospital from 1996 to 2011 was performed. Renal outcome was determined by the Modification of Diet in Renal Disease equation. Disease outcome measures included patient survival and accrual of chronic kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 63 publications
6
31
0
2
Order By: Relevance
“…In our study, more than one third of the patients with active renal AAV had reduced sC3 levels; this subset of patients had a dramatically worse renal prognosis, an observation that is in line with findings of a recently published study (15).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, more than one third of the patients with active renal AAV had reduced sC3 levels; this subset of patients had a dramatically worse renal prognosis, an observation that is in line with findings of a recently published study (15).…”
Section: Discussionsupporting
confidence: 93%
“…A clinical study of a small number of patients revealed that hypocomplementemia was associated with the patient prognosis and with a poor renal prognosis. [6] …”
Section: Introductionmentioning
confidence: 99%
“…The mouse model of anti-MPO IgG-induced NCGN identified an unsuspected role of complement activation [53] that has subsequently been supported by observations in patients [54,55,56,57,58,59]. The NCGN induced by transfer of anti-MPO IgG into wild-type mice or anti-MPO splenocytes into immunodeficient (Rag2-/-) mice could be completely blocked by complement depletion using cobra venom factor [53].…”
Section: Complement In Anca Pathogenesismentioning
confidence: 99%
“…A number of subsequent observations in AAV patients support a role for complement activation in pathogenesis, including evidence for complement activation at tissue sites of vascular inflammation and detection of biomarkers for complement activation in plasma and urine [54,55,56,57,58,59]. For example, the complement membrane attack complex C3d and factor B are detected in the lesion sites of patients with AAV [54].…”
Section: Complement In Anca Pathogenesismentioning
confidence: 99%